Analysis of Indonesian Syariah Financial Institutions Development Strategies - Marthanti, Amas Sari; Santosa, Jaka; Rafik, Ahmad; Ridwan, Wawan; Lahat, Mohammad Amas; Siagian, Sabaruddin (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
The research aims to examine the development strategy of Indonesian Syariah financial institutions. This research focuses on how Indonesian Syariah financial institutions increase their capacity to increase their competitiveness in the Indonesian financial industry. In this research, descriptive research methods were used. Moreover, the data source for this research uses secondary data, which comes from OJK and BPS data. Three decades ago, a Syariah bank, PT. Bank Muamalat Indonesia (BMI). The establishment of this Indonesian Syariah bank was based on intensive requests from thinkers, religious leaders, and Islamic entrepreneurs regarding the importance of accommodating Muslims who wish to make financial transactions in the Indonesian financial industry by applying the principles of Islamic Syariah. After BMI Bank had been operating for several years, the government issued the Banking Law and, in the banking law, recognized the dual system in Indonesian banking, namely, the conventional banking system and the Syariah banking system. Next, the government also issued the Syariah Banking Law to regulate the Syariah banking operational system in Indonesia. Syariah financial institutions have developed from an institutional perspective, with many Syariah banking branch offices, capital markets, and the Syariah non-bank financial industry (IKNB). However, in these three decades, Islamic financial institutions controlled 10 percent of the market share in the Indonesian financial industry. In this research, a strategy was produced to accelerate the capacity of Islamic financial institutions to compete with conventional financial institutions. This research also produced basic (grand), corporate, and functional strategies for accelerating the development of Indonesian Syariah financial institutions.